IMPROVED MUCOADHESIVE PROPERTIES OF THIOLATED PECTIN FILM FOR BUCCAL DELIVERY OF DICLOFENAC - HARTRIANTI, PIETRADEWI; LEONARD, THEODORE EBENEZER; LORENZO, SHERYL; CHRISCENSIA, ERIKA; TRIAVIKA SAHAMASTUTI, AGNES ANANIA (International Journal of Applied Pharmaceutics, 2023)
Objective: This study was aimed to study the effect of degree of esterification (DE) on the thiolation of pectin, the potential to be used as materials for buccal delivery of diclofenac as well as the effect of DE on the physicochemical and mucoadhesive properties of the buccal films. Methods: Low-methoxyl pectin (LMP) and high-methoxyl pectin (HMP) were synthesized into low-methoxyl thiolated pectin (LMTP) and high-methoxyl thiolated pectin (HMTP) by esterification reaction using thioglycolic acid (TGA). The degree of thiolation was evaluated using Ellman’s reaction and FT-IR. Pectins were fabricated into buccal films with diclofenac as a drug model and glycerin as the plasticizer. The obtained films were then studied for swelling and erosion percentage, mucoadhesion time, and in vitro drug release. Results: HMTP and LMTP showed no significant difference in the degree of thiolation regardless of DE (p>0.05). The fabricated LMTP and HMTP films showed significantly higher mucoadhesion time and swelling than HMP and LMP (p<0.05). Moreover, HMTP and LMTP also exhibited sustained release of diclofenac compared to LMP (p<0.05). HMTP showed the highest mucoadhesion time, swelling capacity, and retention of drug release among all groups (p<0.05). Conclusion: Thiolated pectin showed prospective potential to be utilized as a biopolymer for buccal delivery of diclofenac with improved mucoadhesion and controlled drug delivery, regardless of their DE.